Re-evaluating inclusion criteria for autologous hematopoietic stem cell transplantation in advanced systemic sclerosis: Three successful cases and review of the literature. Issue 2 (June 2021) - Shah, Ankoor; Spierings, J; van Laar, JM; Sullivan, Keith M
Systemic sclerosis is a chronic autoimmune disease with a poor prognosis, particularly when a patient has rapidly progressive skin or pulmonary involvement. Autologous hematopoietic stem cell transplant is an emerging treatment for this condition, that has been demonstrated to be more effective than immunosuppressants. Careful selection of patients has reduced the transplant-related mortality and maximized the likelihood of benefit. In this report, we present three cases of successful autologous hematopoietic stem cell transplant in patients who would not have met inclusion criteria for entrance into the completed hematopoietic stem cell transplant. After >18 months of follow-up, three patients had clinically significant benefit in terms of skin tightening and pulmonary function tests. Future studies of hematopoietic stem cell transplant in systemic sclerosis may aim to carefully liberalize inclusion criteria to include patients who may not have otherwise been treated while still maintaining an acceptable safety profile.